DEVELOPMENT OF THE MANAGEMENT OF ORGANIZATIONS, TAKING INTO ACCOUNT THE RISK-BASED APPROACH - I. Avdiiskii, Vladimir; M. Bezdenezhnykh, Vyacheslav; M. Yartseva, Nadezhda (Revista Gênero e Interdisciplinaridade, 2021)
In the formation of new model approaches to analyzing the economy from mega-, macro- to meso- and micro-levels, the shift in the focus of assessing the world, regional and national markets and business from the traditionally limited number of macro-indicators of the state of the economy (GDP, profit, growth rate, inflation, exchange rate etc.) to the analysis of complex indicators of the well-being of society (quality of life, income level of various population groups, quality of education, health care, investment structure, etc.) should be taken into account. One of the main objectives of the study was to find the right risk management tools. For this, cases were analysed in which various methods of managing the socio-economic sphere were used. Myths and stereotypes about the behaviour of people in this area were identified. Risk management is a complex and delicate area of scientific research; therefore, creative thinking was required in adapting the research methodology to get around the difficulties and provide a rich overview for study. The problem of introducing risk-based approach (RBA) both in the processes of analyzing the state and development trends of the economy and in the regulation (control) process in various regulatory scenarios also requires a deep study of these issues both at the methodological and applied levels. This problem has significant differences from the usual tasks of RBA in the problems of analysis and regulation of the development processes of complex socio-economic systems.